The Relationship between Community Religiosity and the Sorong Serah Aji Krame Tradition in Interpreting Marriage Hadiths among the Sasak Community of Central Lombok: Hubungan Religiusitas Masyarakat dengan Tradisi Sorong Serah Aji Krame dalam Interpretasi Hadis-Hadis Pernikahan pada Komunitas Sasak di Lombok Tengah - Alya Farizki Aryandiningrum; Taqnain Taqnain (Takwil: Journal of Quran and Hadith Studies, 2026)
The Sorong Serah Aji Krame tradition is one of the Sasak community’s marriage traditions that is still practiced and is often associated with Islamic values, particularly marriage hadiths. However, studies on how the Sasak community understands, interprets, and represents marriage hadiths within this tradition remain relatively limited. This study aims to analyze the implementation of the Sorong Serah Aji Krame tradition and examine how the Sasak community of Central Lombok understands and practices wedding hadiths within their customary framework. This research focuses on the execution of the tradition, the community’s understanding of matrimonial hadiths, and the extent to which hadith values are reflected in customary practices. Employing a qualitative method with a descriptive-analytical approach to hadith reception, data were collected through in-depth virtual interviews with indigenous leaders, religious figures, and local residents, supported by relevant literature studies. The findings indicate that the Sasak community expresses their understanding of wedding hadith values through four symbolic dimensions. Readiness for marriage is represented through the concepts of nampak lemah and olen, while respect and responsibility toward one's wife are symbolized through sendah lanjaran. The principle of publicizing marriage (I’lan) is reflected through public processions, while the value of simplicity is preserved through customary deliberation mechanisms. These practices appear in four forms: the expression of I’lan values, the verification of marital maturity, the representation of hadith values through cultural symbols, and the transmission of these values across generations. This study concludes that the Sorong Serah Aji Krame tradition reflects community practices that are in accordance with Islamic law, without claiming that customary practices constitute a source or form of Islamic legislation